Simulation of sea level rise in Klang coastlines by using ArcGIS - Siti Fatihah, Kamarudin (2019)
Sea level rise has been recognized as a major threat to coastal habitats and community worldwide. A significant increase of sea level would hamper the economy, trade, tourism, biodiversity, and livelihood. Sea level rise plays a role in flooding, shoreline erosion and hazard from storm which would give great impact especially to low-lying coastal area. In an effort, this study was carried out to identify the risky locations that were affected in year 2030, 2050 and 2100. The selected area was located in Klang, Selangor coastline. Tide events phenomenon, global climate change, anthropogenic factors and coastal flood were among the factors that contribute to the sea level rise. This study was implemented by using Arc Geographical Information System (ArcGIS) software which was a computer-based tool for mapping and analysing things that exist and events that happen on Earth. ArcGIS would generate the data collected from United States Geological Survey‟s (USGS) website, National Hydraulic Research Institute of Malaysia (NAHRIM) and National Hydrographic Centre Malaysia (NHC) which were topography Digital Elevation Model (DEM), sea level rise and high tides data. At the end of the study, ArcGIS has provided the result of inundation area due to sea level rise. In year 2030 and 2050, the total inundated area was same because there were only slightly difference in the increment of projection sea level rise which was 0.115 meter compared to year 2100 which was 0.310 meter. Thus, in year 2100, the total inundated area was bigger than the previous year. The potential inundated area in Klang coastline was mostly all the low-lying area such as Pulau Ketam, Pulau Klang, Pulau Selat Gering, Teluk Gong, Pulau Mat Zain and Port Klang. Mitigation plans were proposed to overcome the sea level rise risk in Klang area which were SAUH revetment and submerged breakwater.